Electrocatalytic Water Oxidation by Single Site and Small Nuclearity Clusters of Cobalt. Issue 4 (1st January 2018) - Swierk, John R.; Tilley, T. Don
Abstract : Cobalt oxides are an earth abundant material that exhibits high electrocatalytic activity for the oxygen evolution reaction (OER) across a wide pH range. Recent studies suggest that OER catalysis can proceed through an active site comprised of one or two cobalt atoms but that multiple adjacent cobalt centers are preferred to stabilize high valent cobalt oxo-intermediates by delocalization. Utilizing molecular precursors to prepare single, isolated cobalt atoms (SS-Co) and small clusters of Co3 O4 we find that OER proceeds more efficiently on Co3 O4 . Using electrochemical impedance spectroscopy (EIS), these results were rationalized at an atomic level. The EIS results support a hypothesis that charge transfer related to the formation of reaction intermediates proceeds more easily on Co3 O4 than on SS-Co, which is attributed to the difficulty in forming Co(IV) = O and unlikely nucleophilic attack by water to form Co(II)-OOH.